Principles of corporate insolvency law - Goode, Royston Miles (Sweet & Maxwell, 2011)
'Principles of Insolvency Law' is widely regarded as 'the' text on Insolvency law. Professor Sir Roy Goode's reputation as the "doyen of commercial law" has established a unique position for the Work as a leading authority in the field. The book provides a clear and concise treatment of the general philosophical principles underpinning Insolvency law. It works as an introduction to this complex area and as such it has a broad market, ranging from students and newly qualified practitioners to barristers in Court